2014
DOI: 10.1039/c4tc00466c
|View full text |Cite
|
Sign up to set email alerts
|

Facile tuning of the aggregation-induced emission wavelength in a common framework of a cyclometalated iridium(iii) complex: micellar encapsulated probe in cellular imaging

Abstract: A series of ‘aggregation induced emission’ active cyclometalated iridium(iii) complexes were synthesized and tested in cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 76 publications
2
36
0
1
Order By: Relevance
“…In the present work, we report the complete synthesis of four novel Ir(III) complexes (1-4) by aliphatic C-H activation of a Schiff base ligand, in line with recent reports on the synthesis of new Ir(III) 11,[19][20][21][33][34][35][36][37] and Pt(II) 38 luminescent complexes. Using both experimental characterization techniques and ab initio quantum chemical calculations we explore the photophysical properties of the synthesized compounds.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present work, we report the complete synthesis of four novel Ir(III) complexes (1-4) by aliphatic C-H activation of a Schiff base ligand, in line with recent reports on the synthesis of new Ir(III) 11,[19][20][21][33][34][35][36][37] and Pt(II) 38 luminescent complexes. Using both experimental characterization techniques and ab initio quantum chemical calculations we explore the photophysical properties of the synthesized compounds.…”
Section: Introductionsupporting
confidence: 82%
“…Complexes 1-4 contain two triphenylphosphine ligands (PPh 3 ) axially coordinated with the Ir(III) atom, since our previous studies suggested that these highly mobile groups could be responsible for the observation of an enhanced emission in aggregated phases. 20,37,77 The four coordination positions on the equatorial plane are occupied by the N and C atoms of a Schiff base bidentate ligand, a chloride, and a hydride ligand. The differences between the four synthesized complexes are in the Schiff base ligand (Scheme 1).…”
Section: Molecular and Electronic Structurementioning
confidence: 99%
“…However, the most extensive studies have been carried out with platinum(II) and gold(I). [28] AIE [29][30][31][32] is an anomalistic phenomenon and the most efficient process for tackling the aggregation-caused quenching (ACQ) [30] effect. In comparison with other luminescent metallic complexes, several distinct advantages have been observed with cyclometalated iridium(III) complexes, for example, superior quantum efficiencies, easy tunability of light emission wavelength, higher thermal and electrochemical stability, and straightforward synthetic routes in comparison with other analogues.…”
Section: Introductionmentioning
confidence: 99%
“…A series of hydride monocyclometalated iridium complexes, which are somehow related to compound 23 , were reported by Laskar and co‐workers . As shown in Figure , the compounds have the general structure [Ir III (CN )(phosphine) 2 (H)(Cl)] (compounds 24 – 36 and 39 ), thus bearing a chromophoric CN cyclometalating ligand and two relatively free‐to‐rotate phosphines located at the apical coordination sites.…”
Section: Aipe In Iriii Complexesmentioning
confidence: 99%